The Role Of Benoa Port In Generating Tourism Business Opportunities In Bali - Ni Wayan Purnami Rusadi; Komang Satya Permadi; Ketma Ayu A. Gabriel (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
As the primary gateway for international cruise ships in Bali, Benoa Port plays a strategic role in driving the maritime tourism economy. This study aims to analyze the port’s contribution to creating tourism business opportunities, particularly for local micro, small, and medium enterprises (MSMEs) amidst the transformation into the Bali Maritime Tourism Hub (BMTH). A descriptive qualitative method was employed, involving field observations, literature reviews, and in-depth interviews with port authorities, MSME actors, and international tourists. The findings indicate that while cruise passenger surged to 54,000 in 2024, creating a significant multiplier effect and spending potential up to IDR 1,000,000 per visitor, structural barriers remain. Critical "service gaps", particularly the limited food and beverage facilities inside the terminal and rigid operational SOPs, hinder MSMEs from fully capturing these economic spillovers. The study concludes that optimizing "soft infrastructure" through flexible vendor licensing and synergistic partnerships is essential to ensure that the BMTH project fosters inclusive and sustainable local economic growth.